Research on the microstructure influence mechanism of hydraulic asphalt concrete based on fuzzy sets - Fang Jianyin; Bian Junhua; Constantinos Soutis; Dang Faning; Qin Yuan; Ren Jie; Gao Jun (Case Studies in Construction Materials)
To investigate the evolution mechanism of micromechanical properties of hydraulic asphalt concrete with varying aggregate content and porosity, a novel method combining CT scanning technology and fuzzy set theory is proposed. This study achieves quantitative partitioning of CT scan maps of asphalt concrete and establishes a numerical model of hydraulic asphalt concrete based on CT numbers. The variation of microcomponents and strength evolution under conditions of λ1→0 and λ2→1 was analyzed. The findings demonstrate that the mesoscale numerical model effectively replicates the microstructural characteristics of hydraulic asphalt concrete, exhibiting interface thickness measurements up to 0.33 mm that show strong concordance with empirical data. Maximum interface rates occur near the convergence point of aggregate-to-binder ratio curves under both λ₁→0 and λ₂→1 boundary conditions. Aggregate content emerges as the primary determinant of compressive strength, while asphalt mortar composition governs plastic deformation characteristics. Structural analysis reveals a distinct phase transition at 38.5 % aggregate ratio: below this threshold, the material maintains a suspension-dense configuration, whereas exceeding it induces transformation into a dense-skeleton architecture. This critical percentage therefore defines the transition boundary between particulate suspension and skeletal packing states. The study further establishes that both power-law and exponential function models effectively characterize peak strength and modulus patterns under extreme λ conditions (λ₁→0 and λ₂→1). This study provides a new approach for analyzing micromechanical properties and mix ratio design of hydraulic asphalt concrete and offers valuable references for designing asphalt concrete rockfill dams.